2021
DOI: 10.1038/s41598-021-98153-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal frequency for magnetic resonant wireless power transfer in conducting medium

Abstract: In this article, we investigated the efficiency of a magnetic resonant wireless power transfer (MR-WPT) in conducting medium and found out an optimal frequency for designing the system. In conducting environment, the eddy current loss is generated by the high-frequency alternating currents in the coils. It is manifested by increased radiation resistance of resonator coil leads to decrease the quality factor (Q-factor), which reduces the wireless power transfer (WPT) efficiency in conducting medium. The Q-facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…State-of-the-art wireless charge transfer techniques have efficiencies of about 40–60%. A coil of 340 cm or 11.15 feet in diameter has a maximum 60% power transfer efficiency while transmitting across 170 cm or 2.2 feet 10 . Such a small distance is extremely unsafe for on-the-go charging in most traffic scenarios and building/hosting such huge coils on both the receiver and the transmitter can be challenging.…”
Section: Related Work and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…State-of-the-art wireless charge transfer techniques have efficiencies of about 40–60%. A coil of 340 cm or 11.15 feet in diameter has a maximum 60% power transfer efficiency while transmitting across 170 cm or 2.2 feet 10 . Such a small distance is extremely unsafe for on-the-go charging in most traffic scenarios and building/hosting such huge coils on both the receiver and the transmitter can be challenging.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Additionally, such solutions require the vehicles to be parked during the charge transaction process leading to a significant loss in BEV road time. Wireless charging schemes such as the one proposed by Kosmanos, D.et al 9 , are hard to implement (cost & feasibility) and will probably be ineffective (wireless charge transfer efficiency is 40–60% at best 10 ).
Figure 1 Description of figures from left to right.
…”
Section: Introductionmentioning
confidence: 99%
“…The outer diameter of the circular spiral is 4.5 cm and the total size of the MM unit cell is 5×5 cm 2 . This design can also be used as a resonator coil for wireless power transfer [40]. An equivalent electrical model MM unit cell is shown in figure 1(b).…”
Section: Magnetic Metamaterials With Negative Permeability and Waveguidementioning
confidence: 99%
“…For more information about multiple load in receiver can see in [18], [19], where several recent studies [20]- [24] talked about different techniques to how to design and get an acceptable result of power transferred wireless and show the result of different ways with simulation results. Also [25] is a modern study MRC-WPT system have suggested to test the effect of conducting medium on efficiency and get a result which is can a method to determine an appropriate frequency of WPT in conducting medium.…”
Section: Table 1 Power and Efficiency Comparison [4] N-n N-s S-n S-s ...mentioning
confidence: 99%